1980
DOI: 10.1175/1520-0477(1980)061<1374:mcc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Meoscale Convective Complexes

Abstract: A particular class of weather system, the Mesoscale Convective Complex (MCC), is identified, defined, and contrasted with other types of convective weather systems. It is found that MCC systems frequently occur over the central United States, grow to tremendous areal extent, and often persist for periods exceeding 12 h. In addition to widespread beneficial rains, a wide variety of severe convective weather phenomena attends these systems. The development and evolution of MCC systems is not explicitly predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
446
1
124

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(580 citation statements)
references
References 23 publications
9
446
1
124
Order By: Relevance
“…On the other hand, many deep convective clouds in such a horizontal scale also appear to the north of the Baiu frontal zone in China where the time-averaged cloud amount is rather smaller than in the Baiu frontal zone, according to the statistical studies by Ninomiya (1989), Takeda and Iwasaki (1987) and Iwasaki and Takeda (1993). The meso-a-scale convective clouds show multiscale structures in which meso-, Q or 7-scale clouds are embedded, and are considered as significant weather systems (Akiyama, 1984a, b;Madox, 1980Madox, , 1983McAnelly and Cotton, 1986;Ninomiya et al , 1981Ninomiya et al , , 1988a. In the present study we simply refer to such meso-a-scale deep convective clouds (including larger meso-/13-scale ones) as the Cb-clusters, although stratiform clouds might be sometimes embedded in them.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, many deep convective clouds in such a horizontal scale also appear to the north of the Baiu frontal zone in China where the time-averaged cloud amount is rather smaller than in the Baiu frontal zone, according to the statistical studies by Ninomiya (1989), Takeda and Iwasaki (1987) and Iwasaki and Takeda (1993). The meso-a-scale convective clouds show multiscale structures in which meso-, Q or 7-scale clouds are embedded, and are considered as significant weather systems (Akiyama, 1984a, b;Madox, 1980Madox, , 1983McAnelly and Cotton, 1986;Ninomiya et al , 1981Ninomiya et al , , 1988a. In the present study we simply refer to such meso-a-scale deep convective clouds (including larger meso-/13-scale ones) as the Cb-clusters, although stratiform clouds might be sometimes embedded in them.…”
Section: Introductionmentioning
confidence: 97%
“…Our 4 km grid spacing model is too coarse to realistically simulate single cell thunderstorms, however, Mesoscale Convective Systems [MCSs, Houze (2004)] that consist of a complex of thunderstorms that become organized, can be captured. In North America, these storms include squall lines (Rotunno et al 1988), which are storms arranged in a line along a evaporatively generated near-surface cold outflow and Mesoscale Convective Complexes with a large circular cloud shield (Maddox 1980). Despite the advantages of CPCSs, a kilometer scale horizontal grid spacing can only resolve large-scale convective motions and has been shown to result in large convective cells that do not entrain midlevel air (Bryan and Morrison 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States (USA), studies of the life cycles of mesoscale convective systems (MCSs) have found that most of these systems initiate in the lee of the Rocky Mountains, move eastward and produce an overnight maximum in precipitation across the central plains, sometimes while undergoing various cycles of regeneration (Maddox, 1980;Fritsch et al, 1986;Augustine and Caracena, 1994;Anderson and Arritt, 1998;Trier et al, 2000). Using Weather Surveillance Radar-88 Doppler (WSR-88D) data, Carbone et al (2002) found that clusters of heavy precipitation display coherent patterns of propagation across the continental USA with span and duration that exceed those of any individual MCS.…”
Section: Introductionmentioning
confidence: 99%